From neutrality to praxis - Araújo, Samuel (Muzikološki zbornik, 2008)
Reflecting upon recent changes in socio-scientific paradigms and thinking over his own research experience with musical communities in Brazil, the researcher presents four case studies in which he finds evidence of a considerable transformation of research scenarios toward growing and more politically charged demands placed by communities upon academics.
Keywords: ethnology; etnologija; etnomuzikologija; politics; politika